THE CULTIVATION OF ENTREPRENEURSHIP VALUES AMONG STUDENTS OF SENIOR HIGH SCHOOL IN DKI JAKARTA (Practitioner Research, 2019)
The unemployment rate of a country, especially an undeveloped one, is a social problem that needs dire attention to be resolved. Entrepreneurship education through schooling system or curriculum is one distinguish effort from the state to reduce unemployment rate. Many research have proved that entrepreneurship education positively reduced the unemployment. The process of introducing and cultivating entrepreneur values inside schooling system are expected to reroute the students life orientation from job seeker to become job creator orientation. This study used qualitative descriptive research method in which the data was collected using semi-structured interviews, observations, and active participatory study documents. Using interactive analysis models, three activities were found to cultivate the entrepreneurship values and they were instruction, extracurricular program, and habituation activities. All three played an important role in the formation of students’ characters and positively contribute in cultivating entrepreneurship values. The results of this research positively contribute to policy making well as on teachers’ perspective on inculcating entrepreneurship values.